Ionic Liquids with More than One Metal: Optical and Electrochemical Properties versus d‐Block Metal Combinations. Issue 72 (3rd December 2020) - Balischewski, Christian; Behrens, Karsten; Zehbe, Kerstin; Günter, Christina; Mies, Stefan; Sperlich, Eric; Kelling, Alexandra; Taubert, Andreas
Abstract: Thirteen N ‐butylpyridinium salts, including three monometallic [C4 Py]2 [MCl4 ], nine bimetallic [C4 Py]2 [M1− x a M x b Cl4 ] and one trimetallic compound [C4 Py]2 [M1− y ‐ z a M y b M z c Cl4 ] (M=Co, Cu, Mn; x= 0.25, 0.50 or 0.75 and y = z= 0.33), were synthesized and their structure and thermal and electrochemical properties were studied. All compounds are ionic liquids (ILs) with melting points between 69 and 93 °C. X‐ray diffraction proves that all ILs are isostructural. The conductivity at room temperature is between 10 −4 and 10 −8 S cm −1 . Some Cu‐based ILs reach conductivities of 10 −2 S cm −1, which is, however, probably due to IL dec. This correlates with the optical bandgap measurements indicating the formation of large bandgap semiconductors. At elevated temperatures approaching the melting points, the conductivities reach up to 1.47×10 −1 S cm −1 at 70 °C. The electrochemical stability windows of the ILs are between 2.5 and 3.0 V. Abstract : Mixed metal tetrahalidometallate ionic liquids (ILs) were for the first time synthesized and studied for their structural, optical, and electrochemical properties. The ILs exhibit high conductivities and tunable optical absorption and are thus novel and highly versatile candidates for application in electronic and optical devices.